1978
DOI: 10.1210/endo-102-5-1576
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Normal Follicles into Thyrotropin-Refractory “Cold” Follicles in the Aging Mouse Thyroid Gland*

Abstract: Autoradiographs of thyroid glands of aging mice demonstrate the gradual appearance of "cold" follicles which fail to iodinate the intraluminar iodoproteins even after intense exogeneous or endogeneous TSH stimulation. "Cold" follicles first appear at the age of 5 months. They may account for 80% of all thyroid follicles in 13-month-old mice. Morphologically, the "cold" follicles are characterized by a larger than normal colloid volume and a comparatively flat epithelium for any given follicle size. Old thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 11 publications
8
34
0
Order By: Relevance
“…In the thyroid of old mice, two types of follicles coexist ('hot' and 'cold' follicles) (21)(22)(23) that reflect the tendency of the thyroid to form multinodular goiter. Based on 125 I autoradiographic studies (21)(22)(23), slowly functioning follicles are characterized by delayed organification and iodine release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the thyroid of old mice, two types of follicles coexist ('hot' and 'cold' follicles) (21)(22)(23) that reflect the tendency of the thyroid to form multinodular goiter. Based on 125 I autoradiographic studies (21)(22)(23), slowly functioning follicles are characterized by delayed organification and iodine release.…”
Section: Discussionmentioning
confidence: 99%
“…Follicles were ranked as 'cold' or 'hot' depending on the aspect of their epithelium and their colloid, according to previous autoradiography studies (21)(22)(23). Variation of the microscopical aspects correlated with various functional states.…”
Section: Morphometrical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using the autoradiographic technique of light microscopic level, STUDER et al (1978) reported that "cold" follicles which appear in the normal mouse thyroid with advancing age, account for 80% of all thyroid follicles in 13-month-old female mice. The present authors wish to use the term "cold" follicle to describe the type of the follicle which dose not respond to intensive injections of exogenous TSH, lacking an ability to accumulate iodine into the follicular lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine Iodine was determined in heart and liver according to Lauber (1975), a method which has been used in this laboratory for previous studies (Studer et al, 1978;Staubli etal., 1983). In principle, determination of iodine is based on incineration of organic material followed by the redox reaction 2 CerNv + Asm = 2 Cer"' + Asv, which is catalyzed by iodide and which can be measured by photometric absorption.…”
Section: Ecg Recordingmentioning
confidence: 99%